Heritage and Democracy : Crisis, Critique, and Collaboration - Daehnke, Jon Darin; Lafrenz Samuels, Kathryn (Book collections on Project MUSE., 2023)
"Examining cultural heritage within the context of democracy. Cultural heritage is a powerful tool in society, capable of producing both social harms as well as social goods and benefits, which can be distributed unevenly via political channels. Reaching across disciplines and national boundaries, this volume examines cultural heritage work within the context of both democratic institutions and democratic practices, including participatory, deliberative, and direct democratic practices. Case studies highlight how democratic politics and cultural heritage shape, impact, and depend upon one another. The rising crisis of democracy across the globe brings these dynamics into sharp relief. The unfinished and fragile nature of democratic politics shines a spotlight on both its shortcomings and its aspirational potential. This is a paradox that heritage practitioners and stakeholders navigate daily, serving as both critics and collaborators of democracy. At the same time that heritage practice embraces participatory approaches, it must also address the challenge of reconciling multiple, often unequal, and frequently incompatible claims for control over heritage. Grappling with democracy's crises also increasingly means recognizing the power of heritage to reinforce or undermine democracy. These essays ask: What are the democratic motives of heritage practice? Why do democracies need heritage? How do the social and cultural referents of heritage infuse democratic practices? Emphasizing the interplay of heritage and democracy in practices and institutions across scales of governance, Heritage and Democracy pinpoints a dynamic that has not been widely examined. A volume in the series Cultural Heritage Studies, edited by Paul A. Shackel"--